(untitled) (Indian Journal of Animal Production and Management, 2014)
Blood profiling is a helpful tool in detecting the health status, metabolic diseases, nutritional deficiencies and welfare of animals. Day old broiler chicks were procured from poultry complex of Orissa Veterinary College, Bhubaneswar. Blood and tissue samples were collected on 15th, 30th , 45th and 60th days of age. The AST activity in liver, brain, muscle and intestine varied from 74.001±6.039 to 85.254±4.631, 88.107±8.223 to 99.870±11.932, 79.611±3.765 to 90.474±6.506 and 91.835±5.708 to 103.164±10.024 mU/L/min/mg respectively. The ALT activity in liver, brain, muscle and intestine varied from 5.387±0.487 to 6.050±0.559, 2.079±0.311 to 3.860±0.583, 1.989±0.452 to 4.442±0.440, 1.544±0.440 to 2.595±0.266 mU/L/ min/mg respectively. The ALP activity in liver, brain, muscle and intestine varied from 36.362±2.232 to 40.000±3.878, 3.477±0.549 to 5.723±1.042, 2.690±0.273 to 5.272±0.891 and 142.676±9.904 to 159.259±14.535 mU/L/min/mg respectively . The ACP activity in liver, brain, muscle and intestine varied from 39.771±4.334 to 52.881±3.994, 14.014±0.408 to 17.596±3.185, 4.392±0.385 to8.492±1.508 and 36.71±31.851 to 53.555±3.934 mU/L/min/mg respectively. The Ach E activity in liver, brain, muscle and intestine varied from 1.883±0.214 to 2.613±0.187, 2.951±0.385 to 3.450±0.305, 2.501±0.359 to 2.501±0.359 and 3.414±0.530 to 3.764±0.489 mU/L/min/mg respectively . The LDH activity in liver, brain, muscle and intestine varied from 1.931±0.134 to 2.565±0.388, 0.918±0.124 to 1.389±0.130, 11.342±1.284 to 13.968±1.017 and 12.233±0.923 to 14.110±1.752 mU/L/min/mg respectively. The serum enzyme activities and metabolites were also estimated from 15th day to 60th day forthnightly. From the present study it can be concluded that the most of the enzyme activities both in serum and tissues varied significantly (P<0.05) with age and almost all the other blood constituents also showed a significant (P<0.05) difference with age.